2005
DOI: 10.1021/jp0512816
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Simulations of an Excited State of X-(H2O)3(X = Cl, I) Complex

Abstract: Upon excitation of Cl(-)(H(2)O)(3) and I(-)(H(2)O)(3) clusters, the electron transfers from the anionic precursor to the solvent, and then the excess electron is stabilized by polar solvent molecules. This process has been investigated using ab initio molecular dynamics (AIMD) simulations of excited states of Cl(-)(H(2)O)(3) and I(-)(H(2)O)(3) clusters. The AIMD simulation results of Cl(-)(H(2)O)(3) and I(-)(H(2)O)(3) are compared, and they are found to be similar. Because the role of the halogen atom in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…Notice that the cyclic structure of water network finally converted into a linear chain structure at t $ 1500 fs. This process is quite similar to the results of Timerghazin and Peslherbe [18] and of Kołaski et al [19]. However, a completely different dynamics was obtained for the iodide atom motion.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Notice that the cyclic structure of water network finally converted into a linear chain structure at t $ 1500 fs. This process is quite similar to the results of Timerghazin and Peslherbe [18] and of Kołaski et al [19]. However, a completely different dynamics was obtained for the iodide atom motion.…”
Section: Resultssupporting
confidence: 90%
“…Timerghazin and Peslherbe [18] have found that the heavy iodide atom was slowly departing from the ðH 2 OÞ À 3 anion cluster although the energy partitioned into the iodide kinetic energy was found to be very small ($0.01 eV). Kołaski et al [19] also found the iodide detachment dynamics in their simulation, where the kinetic energy of the I atom were estimated to be 0.03-0.04 eV. On the other hand, in our BOMD simulation, the iodide atom does not detach from the water cluster but is finally bound to the terminal water molecule in the linear chain ðH 2 OÞ À 4 cluster.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…11). 191 Similarly, one can utilize electric fields to control conformational changes of molecular clusters. Using ab initio study, we investigated geometries, energies, dipole moments, and transition states of the most stable cyclic water clusters with the increasing strength of electric field.…”
Section: 184mentioning
confidence: 99%